Why should children read banned books? (Synergy, 2023)
Sigy George, a high school librarian from India, explores some of the complex history,and reasoning, behind book banning and outlines her views as to why diverse booksshould be read by young people. George considers many examples and her ownexperiences and outlines various reasons for providing access to problematic texts.